Digitalisasi Nilai-Nilai Hindu Studi Komunikasi Budaya Generasi Z di Media Sosial - I Putu Gede Buda Mardiksa Putra; I Nyoman Alit Putrawan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
The advancement of digital technology has fundamentally transformed patterns of cultural and religious communication, particularly among Generation Z, who have grown up within a social media ecosystem. In the Hindu context, digitalisation presents both opportunities and challenges in transmitting core values such as dharma, bhakti, and karma. While previous studies have largely focused on the broader phenomenon of digital religion, a significant research gap remains in examining how Hindu Generation Z constructs, represents, and disseminates cultural values through digital communication practices, particularly within algorithm-driven social media environments. This study aims to analyse the process of digitalisation of Hindu values through the cultural communication practices of Generation Z on social media, as well as to identify the dynamics of meaning that emerge within this context. The research employs a qualitative approach with a descriptive-narrative design. Data were collected through digital ethnography, including observations on platforms such as Instagram, TikTok, and YouTube, alongside content analysis of posts representing Hindu values. Data analysis was conducted using thematic analysis to identify patterns of communication, forms of representation, and evolving constructions of meaning. The findings indicate that Generation Z functions as prosumers, not only consuming but also producing and distributing Hindu values through creative, visual, and interactive digital content. Digitalisation enables the expansion of cultural communication reach; however, it simultaneously encourages the simplification and commodification of sacred values due to the logic of social media algorithms. Furthermore, there is a noticeable shift in religious communication authority from traditional actors to digital figures such as content creators and influencers. The novelty of this study lies in the development of a dharma-based digital cultural communication framework, which explains how Hindu values are negotiated within digital spaces through the interaction of technology, generational dynamics, and culture. This research also offers an integrative perspective that bridges communication studies, sociology of religion, and digital culture within the local Balinese context. It is concluded that digitalisation is not merely a medium, but a dynamic arena for the construction of religious and cultural identity. Therefore, adaptive value-based communication strategies are required to ensure that digital transformation preserves the authenticity of Hindu teachings amidst technological disruption.